MOTIVASI PEMBELAJARAN BAHASA INGGRIS (STUDI KASUS : MAHASISWA JURUSAN BAHASA INGGRIS IAIN METRO) - Halim Adi Kusuma (Jurnal Enterpreneur dan Bisnis (JEBI), 2023)
This research aims to determine the effect of motivation and learning English on students' abilities in the English education study program at IAIN Metro. The research method applied is quantitative descriptive. The population used is 80 students. Data were collected with methods such as documentation, observation and questionnaires. The results of the research indicate that motivation and learning simultaneously affect students' abilities and partially, motivational variables also affect students' abilities. This shows a significant effect and increases student motivation and abilities. The result of the calculated F test is greater than the value of the F table (4.301Ëƒ 3.260). The significant value of F is 0.000 0.019. This shows that H3 is accepted simultaneously so that the motivational and learning variables have a positive impact on students' abilities. The calculated T value of the motivation variable is 2.302 and the T table is 2.006. This shows that T arithmetic T table (2.302 2.006). A significant value of 0.000 0.03 which has a positive coefficient value so that partially X1 has a significant positive impact on students' abilities. The calculated T value for the learning variable is 0.878 and the T table is 2.006. This shows that T count T table (0.878 2.006). The result of the significance value is 0.000 0.03 and the coefficient value is positive. Therefore, the learning variable has an influence on students' abilities